PENINGKATAN KUALITAS PERMUKIMAN KUMUH UNTUK MENDUKUNG WISATA KAMPUNG PELANGI KOTA SEMARANG - Riyulida, Anisa; Sunarti, S (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2019)
Kampung Pelangi is a settlement that was beautified through painting so that it became a tourist village in the city of Semarang, however, it still seemed slum. This causes the settlements to be unfit for the community. Therefore, it is necessary to improve the quality of settlements to alleviate slums and support tourism. This study aims to examine the improvement of the quality of settlements carried out in Kampung Pelangi in its tourism development. The method of analysis uses a quantitative approach with quantitative and qualitative descriptive analysis techniques. The results showed that the settlement quality improvement activities carried out were home improvement and settlement infrastructure. The most significant improvements experienced were changes to the roof of the house and road infrastructure. In this improvement, the socio-economic characteristics of the community have a relationship with the quality improvement activities of the settlements carried out to support Kampung Pelangi tourism. The weakest relationship was found in public education on home improvement activities with a chi-square value of 0.046 and a contingent value of 0.303 coefficient. The condition of this house needs to be further improved in terms of improving house occupancy through developing community capacity to support tourism objects in Kampung Pelangi. In the improvement of settlement infrastructure, the relationship formed was strong enough on the status of the community's house on environmental maintenance activities in Kampung Pelangi with a chi-square value of 0.028 and a coefficient of coefficient of 0.403. Community capacity building needs to be improved in terms of awareness of owning a home privately so that it can play a role in improving infrastructure to support tourism facilities and accessibility. Through the development of this capacity, it will cause the community to play a role in maintaining the quality of their housing and infrastructure. Improving the quality of settlements was developed to support Kampung Pelangi tourism in order to improve the quality of tourism objects, make it easier for tourists to visit, and can increase people's income through tourism activities.